Elucidation of the ion transport mechanisms in CorA, a divalent cation transporter. - Nurhuda Nordin. (2013)
Both Mg2+ and Co2+ are essential ions for organisms, without which pathophysiological effects would occur. A transporter ensures that these ions are kept at a desired concentration within cells and organisms. CorA, which mediates the transport of both Mg2+ and Co2+, is one of the most abundant of such transporters. The CorA family is homologous to eukaryotic Alr1 and Mrs2 magnesium transporters, sharing similar secondary structures, and is thus used as a model for Mg2+ transport. However, the mechanism of its function - how it selects and regulates its substrates, has remained unknown. Earlier, the existence of two subgroups of CorA, subgroups A and B, based on sequence homology was reported. In the recent years, new findings have unveiled substrate preference between the two subgroups of CorA, where a family member of subgroup A has shown to selectively transport Co2+ over Mg2+. Studying the sequence homology between these two subgroups as well as the existing crystal structures, have provided me with new leads into identifying key residues for ion transport. By subjecting these residues to mutagenesis and biochemical studies, I propose a new mechanism by which Thermotoga maritima CorA transports its substrates. The longest helix of CorA rotates and converts the closed hydrophobic gate into an open hydrophilic pore. This rotation is dependent on the cytoplasmic metal binding sites, M1 and M2. In this study, I present data showing that M1 is required mainly for protein stabilization leaving M2 acting as a divalent cation sensor. Lastly, I was able to uncover the molecular mechanisms for how Thermotoga maritima CorA selects for Co2+ over Mg2+. This selection is done through threonine residues inside the channel, as exchange of these residues to serine makes CorA more Mg2+ selective. Since the mechanism of transport proposed here is largely based on conserved amino acids and it is comparable between two CorA belonging to different organisms – Thermotoga maritima and Methanocaldococcus jannaschii, we can extrapolate this mechanism to the rest of the family, hence allowing us to understand better the transport mechanism of this divalent cation transporter family.